Sensitivity analysis of laser welding process by ANFIS methodology - Marsenic, Mladen; Jović, Srđaj (Journal of Production Engineering, 2023)
In this study was analyzed the influence of laser welding parameters on output parameters prediction. Adaptive neuro-fuzzy inference system (ANFIS) was applied for the variable selection process to determine the parameters influence on the lap-shear strength and weld-seam width prediction. The used inputs were: laser power, welding speed, stand-off distance and clamping pressure. Experimental test were used to acquire the training data for the ANFIS network. The ANFIS network was used to predict the lap-shear strength and weld-seam width according to the input variables separately. Root mean square error (RMSE) was used as statistical indicators for comparison. The results from this study could be used as benchmark results in order to improve the laser welding process.